Liraglutide provides neuroprotection by regulating autophagy through the AMPK-FOXO3 signaling pathway in a spinal contusion injury rat model. (16th February 2020) - Zhang, Dongao; Yu, Deshui; Mei, Xifan; Lv, Gang
Highlights: Liraglutide promotes motor function recovery, reduces necrotic cavity and the loss of neurons after spinal contusion. Liraglutide treatment promotes autophagy and autophagic flux in neurons after spinal contusion injury. Liraglutide stimulates the autophagic responses via the AMPK-FOXO3 signaling pathway after spinal contusion injury. Abstract: Spinal cord injury (SCI) induced by trauma is a devasting neurological consequences. Liraglutide, a glucagon-like peptide-1 (GLP-1) analog, has be shown to have neuroprotective effects in several neurodegenerative diseases. However, the potential benefits of liraglutide as well as the underlying mechanisms for its therapeutic benefit for SCI are unclear. We aimed to investigate the therapeutic benefits and decipher the potential signaling pathways of liraglutide in spinal contusion injury. A SD rat model with controlled spinal contusion was established for this study. Behavioral tests and histological examinations were performed to assess the neuroprotective benefits. Several autophagy markers were measured by western blot analysis and immunofluorescence staining, including LC3B, Beclin-1 and p62. In addition, the AMPK-FOXO3 signaling pathway was investigated. Our results demonstrated that liraglutide treatment strongly enhanced motor function recovery and alleviated the degree of necrosis and loss of motor neurons in the spinal cord tissue after contusion. Autophagic responses were activated by liraglutide. LC3B-II/LC3B-I and Beclin-1 expression was enhanced while p62 expression was reduced. In addition, the levels of p-AMPK/AMPK, FOXO3 and p-FOXO3 (phospho S253) were notably up-regulated by liraglutide. These effects were partly reversed by Compound C, an AMPK inhibitor. In summary, our results demonstrated that liraglutide was therapeutically beneficial in treating spinal contusion injury and its underlying mechanism was through the activation of autophagic responses through the AMPK-FOXO3 signaling pathway.